Penetrating into the markets in Eastern Europe and commonwealth of independent states, problems and proposed solutions - Akdağ, Ali Fuat (My University, 1997)
unknown
Keywords: Genel yönetim; PAZARLAMA; Pazarlama yönetimi; ULUSLARARASI PAZARLAMA